A Retrospective Pre-Post Treatment Study of Occupational Therapy Intervention for Children with Sensory Processing Challenges - Sarah A. Schoen; Lucy Jane Miller; Joanne Flanagan (Scholarworks @ WMU, 2018)
Background: This study investigated the impact of an intensive, short-term program that incorporates the principles of sensory integration and relationship-based therapies with extensive parent collaboration. The goals were to identify measures sensitive to change and explore the relation between sensory modulation characteristics and change in behavior after intervention. Method: A retrospective chart review examined routine clinical data pre-post intervention from 179 children identified with sensory processing challenges without comorbid autism. Change in measures of adaptive behavior, emotional functioning, sensory-related behaviors, and motor functioning were evaluated. Relations between sensory modulation and behavior were explored. Results: Improvements were noted from pretreatment to postreatment on all measures of adaptive behavior, problem behaviors, sensory-related functions, and measures of motor function. Sensory craving symptoms were associated with a significant reduction in externalizing and behavior problems after intervention. Conclusion: This study provides preliminary support for the effectiveness of a novel treatment approach.